2006
DOI: 10.1158/0008-5472.can-06-2067
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Prostaglandin E EP Receptors to Inhibit Metastasis

Abstract: It is well established that high cyclooxygenase-2 (COX-2) expression contributes to the aggressive behavior of breast and other malignancies. Due to concerns regarding the safety of long-term use of COX-2 inhibitors as well as a desire to seek more effective alternatives to prevent and treat metastatic disease, we tested the hypothesis that inhibition of downstream signaling by the COX-2 product prostaglandin E 2 (PGE 2 ) would be as effective as inhibiting global prostaglandin synthesis. PGE 2 acts through fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 32 publications
6
95
0
2
Order By: Relevance
“…It has been reported that Gi/o proteins, which are known to affect a variety of cellular functions, activate p-ERK1/2 and subsequent cell proliferation signals [10,32]. AA metabolites are also able to induce cell growth and have been strongly implicated in tumor development [38,39]. Exogenous AA and its lipid metabolites have been shown to induce ERK activation [40].…”
Section: -Test)mentioning
confidence: 99%
“…It has been reported that Gi/o proteins, which are known to affect a variety of cellular functions, activate p-ERK1/2 and subsequent cell proliferation signals [10,32]. AA metabolites are also able to induce cell growth and have been strongly implicated in tumor development [38,39]. Exogenous AA and its lipid metabolites have been shown to induce ERK activation [40].…”
Section: -Test)mentioning
confidence: 99%
“…PGs also act in malignancy growth and metastasis. For example, EP4 signaling through phosphatidylinositol 3-kinase, Erk1 and Erk2 supports growth of CT26 colon carcinoma cells (Hull et al, 2004;Fulton et al, 2006). The potential influence of PGs on mammalian gene expression is emphasized by the revelation of a nuclear PG signaling system in which EP3 receptors are localized in the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with non-steroidal antiinflammatory drugs (NSAIDs) that inhibit COX2 can reduce the risk and incidence of many types of cancer including breast cancer (13). However, in contrast to the serious potential cardiovascular complications of COX2 inhibitors, the direct inhibition of G-protein-linked prostaglandin E2 receptor (EP2) could serve as a much better alternative to COX2 inhibition as a means for breast cancer prevention and treatment (14,15). EP2 couples to Gα s and stimulates cyclic AMP (cAMP) accumulation, protein kinase A (PKA) activation and the phosphorylation of cAMP response element binding protein (CREB), as shown in Fig.…”
Section: Rationale and Hypothesismentioning
confidence: 99%
“…to address this question, one can use genetic, pharmacological and immunological approaches such as a) silence the expression of EP2 and CaR to analyze the compound knockdown by breast cancer cells, b) pharmacological inhibition of EP2 using EP2 antagonists and CaR inhibition by 'calcilytics' (15,(22)(23)(24)(25), and c) inhibition of EP2 and CaR by anti-EP2 and anti-CaR antibodies. The expression of CaR and EP2 can be decreased significantly by using short hairpin RNA (shRNA) in MDA-MB-231 cells.…”
Section: Test Of Hypothesismentioning
confidence: 99%